2000
DOI: 10.1107/s0909049500003137
|View full text |Cite
|
Sign up to set email alerts
|

Time- and space-resolved dynamic studies on ceramic and cementitious materials

Abstract: A review is given of the results and lessons arising from a sustained in situ diffraction study of the structure and performance of functional ceramic/cementitious materials in which synchrotron-based energy-dispersive diffraction has been the central under-pinning technique. Five particular points of discussion emerge: the demands on time resolution; the use of penetrating radiation for the in situ mode; the need for complementary techniques; re-analysing of data; spatially resolved diffraction: a new tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Bensted, 1991;Brown, 1993;Stu È rmer et al, 1994) that the hydration of brownmillerite in real (i.e. impure) Portland cements appears to be surprisingly slow up to about 343 K, above which the hydration kinetics are controlled more by the temperature than the choice of retarding system (Barnes et al, 2000). Monitoring the hydration of brownmillerite using multi-angle energy-dispersive diffraction intensities: (a) production of ettringite (using the 100 peak; bottom detector); (b) the loss of brownmillerite (using the 020 peak; bottom detector).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bensted, 1991;Brown, 1993;Stu È rmer et al, 1994) that the hydration of brownmillerite in real (i.e. impure) Portland cements appears to be surprisingly slow up to about 343 K, above which the hydration kinetics are controlled more by the temperature than the choice of retarding system (Barnes et al, 2000). Monitoring the hydration of brownmillerite using multi-angle energy-dispersive diffraction intensities: (a) production of ettringite (using the 100 peak; bottom detector); (b) the loss of brownmillerite (using the 020 peak; bottom detector).…”
Section: Discussionmentioning
confidence: 99%
“…These sum-plots illustrate the value of expressing the intensities as a function (i.e. 1/d) of d spacing for the purpose of identifying suitable peak±detector combinations for various time-resolved analyses (composition, density) on the whole sample (Barnes et al, 2000). Fig.…”
Section: Hydration Behaviour and Multi-angle Energy-dispersive Difframentioning
confidence: 99%
“…[20,22] The time-resolved energy-dispersive X-ray diffraction (EDXRD) technique at the Daresbury SRS was used for the study reported here. For over a decade, it has proved its efficiency in looking at the crystallization of a variety of microporous materials including zeolites and phosphates, [23][24][25] the behavior of minerals [26] and cements [27] under hydrothermal conditions, and the investigation of the intercalation of molecules and ions into layered solids. [28,29] The main advantage of EDXRD over other time-resolved diffraction techniques lies in the use of intense, white-beam X-rays over a wide energy range.…”
mentioning
confidence: 99%
“…This single factor was responsible for the undesirably long data collection times. These were significantly shorter than the 20 hours point by point scans previously described (Barnes et al 2000) but were typically 2-3 hours. This would allow the study of a thin alloy sample for use in aerospace engineering applications, but would not be suitable for studying a biopsy sample owing to radiation damage problems.…”
Section: Discussionmentioning
confidence: 67%